IMPLEMENTASI UPAH MINIMUM KOTA DALAM MENINGKATKAN KESEJAHTERAAN PEKERJA DI KOTA KENDARI (Studi di Kota Kendari) - Zulfikar Putera (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2019)
The implementation of Kendari City Minimum Wage has not gone well, there is no regulation that can accommodate the interests of workers and companies, the interpretation that minimum wages are basic wages and other benefits wages need to be continued that the minimum wage is the basic wage other than the wages of other benefitsKeyword : Minimum Wage, Welfare